Intensive Care Management of Anaphylactic Shock Secondary to Wasp Stings: A Case Report - I Made Eryana; Ni Luh Putu Winda Alpiniawati; Dewa Ayu Rina Wana; I Gede Putu Jarwa Antara (Open Access Indonesian Journal of Medical Reviews, 2024)
Anaphylactic shock is a life-threatening allergic reaction that requires immediate medical intervention. Wasp stings are a common trigger for anaphylaxis, and rapid administration of epinephrine is crucial in preventing fatal outcomes. This case report describes the successful intensive care management of a patient who developed anaphylactic shock following multiple wasp stings. A 51-year-old female presented to the emergency department with anaphylactic shock after being stung by multiple wasps. She exhibited severe angioedema, hypotension, and tachycardia. Immediate treatment included intramuscular epinephrine, intravenous corticosteroids, antihistamines, and fluid resuscitation. The patient was transferred to the intensive care unit (ICU) for close monitoring and supportive care. In conclusion, this case highlights the importance of prompt recognition and treatment of anaphylactic shock, particularly the administration of epinephrine. It also emphasizes the role of ICU monitoring in managing severe allergic reactions and preventing complications.